2010
DOI: 10.1016/j.neulet.2010.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Type III intermediate filament peripherin inhibits neuritogenesis in type II spiral ganglion neurons in vitro

Abstract: Peripherin, a type III intermediate filament protein, forms part of the cytoskeleton in a subset of neurons, most of which have peripheral fibre projections. Studies suggest a role for peripherin in axon outgrowth and regeneration, but evidence for this in sensory and brain tissues is limited. The exclusive expression of peripherin in a sub-population of primary auditory neurons, the type II spiral ganglion neurons (SGN) prompted our investigation of the effect of peripherin gene deletion (pphKO) on these neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
1
13
0
1
Order By: Relevance
“…Peripherin is a neuronal differentiation marker induced by stimulation with NGF that has been suggested to have a role in neuritogenesis, axonal outgrowth and axonal regeneration [2, 4, 11, 43, 48, 56, 86]. Importantly, overexpression of peripherin causes degeneration of motor axons during aging inducing neuron dysfunction and the slowing down of neurofilament protein transport [10, 58, 67].…”
Section: Discussionmentioning
confidence: 99%
“…Peripherin is a neuronal differentiation marker induced by stimulation with NGF that has been suggested to have a role in neuritogenesis, axonal outgrowth and axonal regeneration [2, 4, 11, 43, 48, 56, 86]. Importantly, overexpression of peripherin causes degeneration of motor axons during aging inducing neuron dysfunction and the slowing down of neurofilament protein transport [10, 58, 67].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work had proposed that both types of SGN neurons innervate both types of hair cells transiently in early development but then undergo refinement leading to the final innervation pattern (Rontal and Echteler, 2003). It has been speculated that this sorting mechanism is driven by expression of the protein Peripherin in type II SGNs in early postnatal stage (Barclay et al, 2010; Huang et al, 2007; Lallemend et al, 2007). However, type II fiber growth is normal in Peripherin knockout mice, suggesting Peripherin protein is not required for the innervation pattern in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…However, type II fiber growth is normal in Peripherin knockout mice, suggesting Peripherin protein is not required for the innervation pattern in vivo. Nevertheless, absence of Peripherin protein seems to affect elongation of type II fibers in vitro (Barclay et al, 2010). Furthermore, with the technique to selectively label subpopulations of SGNs, it was shown that no fibers innervating both inner and outer hair cells could be found even at E16.5 (Koundakjian et al, 2007) before Peripherin protein has been detected in spiral ganglion neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, care must be taken when drawing conclusions about selectivity in expression, since this might depend on dynamic factors within the neuron population. PP expression and re-expression has been linked to nerve growth during development and axon regeneration (Gorham et al 1990;Troy et al 1990aTroy et al , 1990bOblinger et al 1989;Wong and Oblinger 1990;Terao et al 2000) and during repair (Oblinger et al 1989;Troy et al 1990b;Chadan et al 1994;Helfand et al 2003;Lallemend et al 2007) and can be induced by neurotrophic factors (Thompson and Ziff 1989;Lecomte et al 1998;Barclay et al 2010). The marked differences in PP immunoreactivity between pig and man could therefore theoretically be attributable to changes related to fixation time.…”
Section: Discussionmentioning
confidence: 99%
“…PP has been found to be mainly expressed in postnatal and adult animals by type II spiral ganglion neurons (Romand et al 1990;Berglund and Ryugo 1991;Kuijpers et al 1991;Ylikoski et al 1993;Hafidi 1998;Schimmang et al 2003;Barclay et al 2010). Its restricted distribution in type I cells, either as weaker staining (Kuijpers et al 1991;Ylikoski et al 1993) or as occurring in a few cells in the extreme basal portion (Berglund and Ryugo 1991), has also been reported.…”
Section: Introductionmentioning
confidence: 99%